Development and Validation of Fiber Bragg Grating Sensing Pad for Interface Pressure Measurements Within Prosthetic Sockets - Al-Fakih, E.A.; Abu Osman, Noor Azuan; Adikan, Faisal Rafiq Mahamd; Eshraghi, A.; Jahanshahi, P. (Institute of Electrical and Electronics Engineers (IEEE), 2016)
This paper presents an efficient fiber Bragg grating (FBG)-based sensing pad that is capable of measuring the interface pressure within prosthetic sockets, and exhibits required sensitivity, enhanced durability, and the lowest possible hysteresis error. Three key fabrication parameters were studied to assess their effects on the performance of different sensing pad designs. These parameters included the FBG embedding depth (top, bottom, and neutral layers of the sensing pad), the sensing pad thickness (1, 2, and 3 mm), and finally, different embedding materials. Each sensing pad was studied while attached to Pe-lite and silicone prosthetic liners. Afterward, the sensing pad design that exhibited the best performance was employed to fabricate an expandable array of FBGs for interface pressure measurements within prosthetic sockets. One transtibial amputee participated in this paper to further assess the in situ performance of the sensing pad. To validate the findings, the results were also compared with the pressure measurements using the F-socket sensors. The results revealed that the FBGs embedded in the neutral layer of harder and thicker sensing pads exhibited the highest sensitivity as well as excellent accuracy. In addition, they could successfully measure the interface pressure inside the prosthetic socket. Higher pressure values were logged by the FBG sensors compared with the F-socket. Yet, the trend of pressure changes was similar for both sensor types. This paper is hoped to form a robust platform for the researchers intending to utilize the FBG sensors in such applications.